2006
DOI: 10.1105/tpc.105.039719
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive Expression Exposes Functional Redundancy between the Arabidopsis Histone H2A Gene HTA1 and Other H2A Gene Family Members

Abstract: The Arabidopsis thaliana histone H2A gene HTA1 is essential for efficient transformation of Arabidopsis roots by Agrobacterium tumefaciens. Disruption of this gene in the rat5 mutant results in decreased transformation. In Arabidopsis, histone H2A proteins are encoded by a 13-member gene family. RNA encoded by these genes accumulates to differing levels in roots and whole plants; HTA1 transcripts accumulate to levels up to 1000-fold lower than do transcripts of other HTA genes. We examined the extent to which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
93
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 100 publications
(97 citation statements)
references
References 82 publications
(101 reference statements)
4
93
0
Order By: Relevance
“…Mutant Arabidopsis lines containing T-DNA insertions in or near several other core histone genes, including HTA2, HTA3, HTA11, HTB5, HTB6, HTR5/4, HFO3, and HFO4, also reduced transformation frequency to various extents (Zhu et al, 2003b), although we have not yet determined the specific stage of transformation that was disrupted. Our observations that overexpression of HTA1 increased transformation frequency (Mysore et al, 2000a;Yi et al, 2006) suggested to us that increased T-DNA integration may be the cause of this hypersusceptibility to Agrobacterium-mediated transformation. However, the results of this study and other work (L.-Y.…”
Section: Discussion Several Arabidopsis Histone Genes Enhance Agrobacmentioning
confidence: 87%
See 4 more Smart Citations
“…Mutant Arabidopsis lines containing T-DNA insertions in or near several other core histone genes, including HTA2, HTA3, HTA11, HTB5, HTB6, HTR5/4, HFO3, and HFO4, also reduced transformation frequency to various extents (Zhu et al, 2003b), although we have not yet determined the specific stage of transformation that was disrupted. Our observations that overexpression of HTA1 increased transformation frequency (Mysore et al, 2000a;Yi et al, 2006) suggested to us that increased T-DNA integration may be the cause of this hypersusceptibility to Agrobacterium-mediated transformation. However, the results of this study and other work (L.-Y.…”
Section: Discussion Several Arabidopsis Histone Genes Enhance Agrobacmentioning
confidence: 87%
“…Increasing evidence indicates that these histone variants have specialized functions; therefore, their incorporation into chromatin at specific regions of the genome or loci may confer specific regulatory or structural features (Kamakaka and Beggins, 2005;March-Diaz et al, 2008;Jin et al, 2009). Histone H2A has the largest number of variants, which include H2A-X (Arabidopsis HTA3 and HTA5) and H2A-Z (Arabidopsis HTA8, HTA9, and HTA11; Raisner and Madhani, 2006;Yi et al, 2006). In plants, as in other eukaryotes, histone H3 variants include H3.2 and H3.3 (Arabidopsis HTR12), which is found in the centromeric region.…”
Section: Discussion Several Arabidopsis Histone Genes Enhance Agrobacmentioning
confidence: 99%
See 3 more Smart Citations